COVID-19 Recommendations From Ophthalmic and Plastic Reconstructive Surgery Societies Worldwide. Issue 4 (July 2020) - Nguyen, Anne X.; Gervasio, Kalla A.; Wu, Albert Y.
Abstract : Purpose: The COVID-19 pandemic has brought unprecedented challenges for oculoplastic surgeons worldwide, in terms of care delivery, medical equipment and at-risk patient management. To date, there are no centralized or compiled international COVID-19 guidelines for oculoplastic surgeons. Methods: We examined COVID-19 guidelines published by oculoplastic societies worldwide. All countries around the world were initially considered in this study, but only 9 oculoplastic societies met the inclusion criteria: (1) publicly available guidelines displayed on the oculoplastic society's website, or (2) guidelines received from the oculoplastic society after contacting them twice using the contact information on their website. Results: The 9 oculoplastic societies examined include: the American Society of Ophthalmic Plastic and Reconstructive Surgery, the British Oculoplastic Surgery Society, the Canadian Society of Oculoplastic Surgery, the European Society of Ophthalmic Plastic and Reconstructive Surgery, la Sociedad Española de Cirugía Plástica Ocular y Orbitaria, la Asociación Colombiana de Cirugía Plastica Ocular, the Asia Pacific Society of Ophthalmic Plastic & Reconstructive Surgery, the Oculoplastics Association of India, and the Philippine Society of Ophthalmic Plastic and Reconstructive Surgery. They all agree that urgent procedures should not be delayed, while non-necessary procedures (including all elective clinic services) should be postponed. When adequate protective equipment is available, oculoplastic surgeons must treat urgent cases. Eight out of 9 societies have provided recommendations on personal protective equipment use in order to prevent the spread of COVID-19 and to adequately protect mucous membranes. Other recommendations provided by certain societies are related to shelter in place measures, hand hygiene and surface disinfection protocols, patient triage, and thyroid eye disease management. Conclusions: All 9 societies with published recommendations have provided valuable recommendations to their members, regarding urgency of care and infection control solutions (personal protective equipment, hand hygiene, telemedicine, and social isolation). Abstract : Nine major oculoplastic societies have issued recommendations related to proper patient care, social distancing, and personal protective equipment use, to ensure that oculoplastic surgeons adopt the best clinical and hospital-based practices during the COVID pandemic.Supplemental Digital Content is available in the text.